2013
DOI: 10.1016/j.jpsychires.2012.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal volume and total cell numbers in major depressive disorder

Abstract: Neuroimaging consistently reveals smaller hippocampal volume in recurrent or chronic major depressive disorder (MDD). The underlying cellular correlates of the smaller volume are not clearly known. Postmortem tissues from 17 pairs of depressed and control subjects were obtained at autopsy, and informant-based retrospective psychiatric assessment was performed. Formalin-fixed left temporal lobes were sectioned (40 μm), stained for Nissl substance, and every 60th section selected throughout the entire hippocampu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
76
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(91 citation statements)
references
References 47 publications
10
76
0
Order By: Relevance
“…Furthermore, a recent in-vivo MRI study we performed (Huang et al, 2013) and post-mortem studies (Boldrini et al, 2013), reported increased DG volume and increased DG granule cell and glial cell numbers (Cobb et al, 2013) in MDD patients treated with antidepressants. These findings are consistent with the suggestion that stimulating DG neurogenesis with antidepressants might play an important role in reversing HC volume reduction in MDD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent in-vivo MRI study we performed (Huang et al, 2013) and post-mortem studies (Boldrini et al, 2013), reported increased DG volume and increased DG granule cell and glial cell numbers (Cobb et al, 2013) in MDD patients treated with antidepressants. These findings are consistent with the suggestion that stimulating DG neurogenesis with antidepressants might play an important role in reversing HC volume reduction in MDD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies volume reductions of the hippocampus were shown to correlate with duration of untreated illness, suggesting that they may represent long-term consequences rather than predict illness onset (Cobb et al, 2013; MacQueen et al, 2003; Sheline, Sanghavi, Mintun, & Gado, 1999). However, a recent meta analysis of studies investigating first episode depression has found volume losses that are consistent with the neurotrophic deficit hypothesis of MDD (Cole, Costafreda, McGuffin, & Fu, 2011).…”
Section: Gabaergic Transmission In Relation To the Neurotrophic Dementioning
confidence: 99%
“…Some studies suggest that brain volume reduction in MDD is due to loss of neurons and/or glia (Drevets, Price, & Furey, 2008; Miguel-Hidalgo & Rajkowska, 2002). However, more recent data suggest that brain volume reduction in MDD is predominantly due to reductions in neuropil rather than cell numbers (Cobb et al, 2013). …”
Section: Gabaergic Transmission In Relation To the Neurotrophic Dementioning
confidence: 99%
“…A meta-analysis of 32 magnetic resonance imaging (MRI) studies suggests about a 4 percent smaller left hippocampal volume in patients with a history of multiple episodes of depression or duration of illness exceeding 2 years (McKinnon et al, 2009). Our group recently published a stereological assessment of the volume of the postmortem hippocampus in chronic/recurrent depression and noted that total volume was decreased with increasing duration of illness (Cobb et al, 2013). We sought to determine whether the change in volume in MDD was due to altered neuronal or glial number, density or soma size.…”
Section: Introductionmentioning
confidence: 99%